Ionized oxygen vacancy-related electrical conductivity in (Pb(1-x)La(x)) (Zr(0.90)Ti(0.10))(1-x/4)O(3) ceramics - Pelaiz-Barranco, A. [UNESP]; Guerra, J. D. S. [UNESP]; Lopez-Noda, R.; Araujo, E. B. [UNESP] (Iop Publishing Ltd, 2008)
The electrical conductivity behaviour in the paraelectric state has been investigated in lanthanum modified lead zirconate titanate (PLZT) ceramics, considering the universal relaxation law. The contribution of conductive processes to the dielectric response for the low-frequency range was discussed taking into account the oxygen vacancies mechanism. The activation energies for the thermally hopping and conductivity processes were obtained. The results for the frequency dependence of the conductivity suggest at the oxygen vacancy hopping processes, due to relaxations in oxygen vacancy-related dipoles, being mainly responsible for the conduction behaviour in the studied system.